EDEN ISS Rack-like food production unit: results after mission in Antarctica - Boscheri, Giorgio; Lobascio, Cesare; Zabel, Paul; Marchitelli, Giovanni; Saverino, Antonio (49th International Conference on Environmental Systems, 2019)
Giorgio Boscheri, Thales Alenia Space Italia, Italy Cesare Lobascio, Thales Alenia Space - Italia, Italy Paul Zabel, German Aerospace Center (DLR), Germany Giovanni Marchitelli, Thales Alenia Space Italia, Italy Antonio Saverino, Thales Alenia Space Italia, Italy ICES204: Bioregenerative Life Support The 49th International Conference on Environmental Systems as held in Boston, Massachusetts, USA on 07 July 2019 through 11 July 2019. Plant cultivation in large-scale closed environments is challenging and several key technologies necessary for space-based plant production are not yet space-qualified or remain in early stages of development. The Horizon2020 EDEN ISS project aims at development and demonstration of higher plant cultivation technologies, suitable for near term deployment on the International Space Station (ISS) and, in a longer term perspective, within Moon and Mars habitats. The EDEN ISS consortium, as part of the performed activities, has designed and built a plant cultivation system having form, fit and function of a European Drawer Rack 2 (EDR II) payload, with a modularity that would allow its incremental installation in the ISS homonymous rack, occupying from one-quarter rack to the full system. The developed system, named RUCOLA (Rack-like Unit for Consistent on-orbit Leafy crops Availability) was completed and tested in a laboratory environment in early 2017. The system was then operated in the highly-isolated German Antarctic Neumayer Station III, in a container-sized test facility to provide realistic mass flow relationships and interaction with a crewed environment. This paper describes the key results of the RUCOLA plant growth facility tests in Antarctica as a space-analogue environment.